Seed predation of forest species in the southern Amazon - Garlet, Juliana; Melo, Roseline da Silva (Seven Editora, 2024)
Seed production is an important stage in the biological cycle of plants. However, insects can interrupt this cycle, directly attacking fruits and seeds, which can influence the abundance and distribution of species. Insects are considered the main responsible for seed predation, and the main spermatophagous Orders are: Diptera, Hymenoptera, Coleoptera and Lepidoptera. In this way, the aim of this study was to identify the insects that attack the seeds sold by the Rede de Sementes do Portal da Amazônia. This analysis was carried out with seed samples sent by the seed network, and also through bibliographical research searching for predation records for species sold by the Seed Network. The groups of spermatophagous insects that were present in forest species were identified, identifying them at the level of Order, Family, Subfamily and, when possible, species. Thus, it was found that predation by these insects occurred on seeds of 15 forest species from seed houses and 12 species that are part of the list of species offered by the seed network. The main orders identified causing damage were: Coleoptera and Lepidoptera, showing a greater predominance of attack by coleoptera. Thus, there was a significant attack and record of spermatophagous insects on the seeds of native forest species in the region, mainly from the order Coleoptera. DOI:https://doi.org/10.56238/sevened2024.007-076